Can clinical CT data improve forensic reconstruction? - Schuh, Petra; Scheurer, Eva; Fritz, K.; Pavlic, M.; Hassler, E.; Rienmüller, R.; Yen, Kathrin (International journal of legal medicine, 2013)
In accidents resulting in severe injuries, a clinical forensic examination is generally abandoned in the initial phase due to high-priority clinical needs. However, in many cases, data from clinical computed tomography (CT) examinations are available. The goals of this prospective study were (a) to evaluate clinical CT data as a basis for forensic reconstruction of the sequence of events, (b) to assess if forensic radiological follow-up reading improves the forensic diagnostic benefit compared to the written clinical radiological reports, and (c) to evaluate if full data storage including additional reconstructed 0.6-mm slices enhances forensic analysis. Clinical CT data of 15 living individuals with imaging of at least the head, thorax, and abdomen following polytrauma were examined regarding the forensic evaluation of the sequence of events. Additionally, 0.6-mm slices and 3D images were reconstructed for forensic purposes and used for the evaluation. At the forensic radiological readings, additional traumatic findings were observed in ten of the 15 patients. The main weakness of the clinical reports was that they were not detailed enough, particularly regarding the localization of injuries and description of wound morphology. In seven cases, however, forensic conclusions were possible on the basis of the written clinical reports, whereas in five cases forensic reconstruction required specific follow-up reading. The additional 0.6-mm slices were easily available and with improved 3D image quality and forensic diagnostics. In conclusion, the use of clinical CT data can considerably support forensic expertise regarding reconstruction issues. Forensic follow-up reading as well as the use of additional thin slices for 3D analysis can further improve its benefit for forensic reconstruction purposes.